The effect of 10-week isokinetic training on muscle strength and gymnastic performance in preadolescent female gymnast - Dallas, G. C.; Dallas, C.; Maridaki, M. (Science of Gymnastics Journal, 2021)
The purpose of this study was to investigate the effect of isokinetic training on muscle strength and gymnastic performance when added to traditional gymnastic training on handspring vault in preadolescent female gymnasts. Twenty female gymnasts with a mean age of 10.50 ± 1.19 years, height 125.50 ± 4.52cm, and body mass 27.30 ± 2.58 kg volunteered to participate in this study. A Cybex II Isokinetic dynamometer was used to measure the peak torque of the knee joint in extension at angular velocities of 60°/sec and 300°/ sec. A Casio EX-F1 (Tokyo, Japan) high speed video camera was placed perpendicular to the optical axis of springboard and vaulting horse. The subjects participated in 10-weeks training for three non-consecutive days per week, 2 hours per day, and separated into two equal groups. The experimental group (EG) followed a specialized training program (technical preparation and muscle strength via Cybex II), whereas the control group (CG) followed the traditional training program (technical preparation and muscle strength). Results showed no significant interaction was found for gymnastic score; however, a significant main effect was found for the time. No significant interaction effect among the three independent variables (group, time, side) was found for the knee extension at 60°/sec. However, the EG had a significantly higher mean values compared to the CG in the post-test. The interaction among the three independent variables with respect to the knee flexion at 300°/sec was not significant. However, the interaction between sides by group was significant. The 10-week isokinetic training added to the traditional training improved the knee strength, which consequently improved aspects of the vault, but did not affect other technical aspects of the handspring performance. Furthermore, results of our study support the claim that optimal performance is the result of a complex interaction of several factors.